Comprehensive investigation of RNF213 nonsynonymous variants associated with intracranial artery stenosis - Hongo, Hiroki; Miyawaki, Satoru; Imai, Hideaki; Shimizu, Masahiro; Yagi, Shinichi; Mitsui, Jun; Ishiura, Hiroyuki; Yoshimura, Jun; Doi, Koichiro; Qu, Wei; Teranishi, Yu; Okano, Atsushi; et al. (Scientific reports, 2020)
Intracranial artery stenosis (ICAS) is the most common cause of ischemic stroke worldwide. RNF213 single nucleotide variant c.14429G > A (p.Arg4810Lys, rs112735431) was recently reported to be associated with ICAS in East Asians. However, the disease susceptibility of other RNF213 variants has not been clarified. This study comprehensively investigated ICAS-associated RNF213 variants in a pool of 168 Japanese ICAS patients and 1,194 control subjects. We found 138 nonsynonymous germline variants by target resequencing of all coding exons in RNF213 . Association study between ICAS patients and control subjects revealed that only p.Arg4810Lys had significant association with ICAS (P = 1.5 × 10 –28 , odds ratio = 29.3, 95% confidence interval 15.31–56.2 [dominant model]). Fourteen of 138 variants were rare variants detected in ICAS patients not harboring p.Arg4810Lys variant. Two of these rare variants (p.Cys118Arg and p.Leu2356Phe) consistent with variants previously reported in moyamoya disease patients characterized by stenosis of intracranial artery and association with RNF213 , and three rare variants (p.Ser193Gly, p.Val1817Leu, and p.Asp3329Tyr) were found neither in control subjects and Single Nucleotide Polymorphism Database. The present findings may improve our understanding of the genetic background of intracranial artery stenosis.